2018
DOI: 10.5021/ad.2018.30.1.8
|View full text |Cite
|
Sign up to set email alerts
|

HLA-C*17, DQB1*03:01, DQA1*01:03 and DQA1*05:05 Alleles Associated to Bullous Pemphigoid in Brazilian Population

Abstract: BackgroundBullous pemphigoid (BP) is an autoimmune disease with bullous vesicles and an incidence of 0.2 to 1.4 per 100,000 inhabitants. Many studies have been published demonstrating the association of pemphigoid with HLA class II system alleles in different populations, however there are no data on the BP, one of the most heterogeneous in the world.ObjectiveTo typify HLA alleles in Brazilians with Bullous pemphigoid.MethodsThe study group included 17 Brazilian patients with a confirmed diagnosis of BP from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 19 publications
1
20
0
1
Order By: Relevance
“…Research has also shown that HLA-DQB1*0301 is related to BP and mucous membrane pemphigoid (MMP) [ [82] , [83] , [84] , [85] ]. Dipeptidyl peptidase-4 (DPP-4) inhibitor, a class of drugs commonly used for the treatment of type 2 diabetes, is considered as to be an inducer of BP.…”
Section: Bullous Pemphigoidmentioning
confidence: 99%
“…Research has also shown that HLA-DQB1*0301 is related to BP and mucous membrane pemphigoid (MMP) [ [82] , [83] , [84] , [85] ]. Dipeptidyl peptidase-4 (DPP-4) inhibitor, a class of drugs commonly used for the treatment of type 2 diabetes, is considered as to be an inducer of BP.…”
Section: Bullous Pemphigoidmentioning
confidence: 99%
“…Interestingly, DQB1 *03:01 has been reported as a susceptibility allele in another dermatological disease: bullous pemphigoid, an organ-specific autoantibody-mediated autoimmune blistering skin disorder in normal patients and in type 2 diabetes mellitus patients receiving dipeptidyl peptidase-IV inhibitors [ 22 , 39 , 40 , 41 , 42 ]. The mechanism of this association is still unclear, but it has been proposed that DQB1 *03:01 could bind bullous pemphigoid 180 (BP180, BP antigen 2, collagen XVII), which may lead to cutaneous disease [ 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The HLA class II DQB1*03:01 allele is more prevalent in Caucasian patients with BP than in the general population and has also been associated with neurological diseases. 37,38…”
Section: Bullous Pemphigoidmentioning
confidence: 99%